Modernization of Islamic Education in North Sumatra: Thoughts and Contributions of Sheikh Ali Hasan Ahmad Ad-Dary - Nasution, Fauziah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is a figure study research, the purpose is to produce a formulation of analysis of the biography, thoughts, and contributions of Sheikh Ali Hasan regarding the modernization of Islamic education in North Sumatra. The primary data source of this research is the intellectual works of Sheikh Ali Hasan Ahmad Ad-dary in the form of books, as well as the Islamic education institutions that were developed. The secondary sources of this research are the works of other people about him. The research stages include data collection, data verification, interpretation, and preparation of research reports on character studies. The data analysis used is content analysis. The research findings show that the educational modernization of Sheikh Sheikh Ali Hasan Ahmad Ad-dary's includes: developing a culture of literacy by producing forty-four written works covering the fields of Fiqh and Islamic Law, Hadith studies, Al-Quran studies, morals and theology, and even actual Islamic issues. In addition, he also pioneered the study of Hadith in North Sumatra and pioneered and developed higher education institutions in North Sumatra. The thought, role, and contribution of Sheikh Ali Hasan Ahmad Ad-dary in the modernization of Islamic education in North Sumatra is a historical fact that cannot be denied until now. Therefore, the study of